Anthropology in public health emergencies: what is anthropology good for?. Issue 2 (25th March 2018) - Stellmach, Darryl; Beshar, Isabel; Bedford, Juliet; du Cros, Philipp; Stringer, Beverley
Abstract : Recent outbreaks of Ebola virus disease (2013–2016) and Zika virus (2015–2016) bring renewed recognition of the need to understand social pathways of disease transmission and barriers to care. Social scientists, anthropologists in particular, have been recognised as important players in disease outbreak response because of their ability to assess social, economic and political factors in local contexts. However, in emergency public health response, as with any interdisciplinary setting, different professions may disagree over methods, ethics and the nature of evidence itself. A disease outbreak is no place to begin to negotiate disciplinary differences. Given increasing demand for anthropologists to work alongside epidemiologists, clinicians and public health professionals in health crises, this paper gives a basic introduction to anthropological methods and seeks to bridge the gap in disciplinary expectations within emergencies. It asks: 'What can anthropologists do in a public health crisis and how do they do it?' It argues for an interdisciplinary conception of emergency and the recognition that social, psychological and institutional factors influence all aspects of care.